3,4-methylenedioxymethamphetamine (MDMA): current perspectives - Meyer JS (Dove Medical Press, 2013)
Jerrold S Meyer Department of Psychology, Neuroscience and Behavior Program, University of Massachusetts, Amherst, MA, USA Abstract: Ecstasy is a widely used recreational drug that usually consists primarily of 3,4-methylenedioxymethamphetamine (MDMA). Most ecstasy users consume other substances as well, which complicates the interpretation of research in this field. The positively rated effects of MDMA consumption include euphoria, arousal, enhanced mood, increased sociability, and heightened perceptions; some common adverse reactions are nausea, headache, tachycardia, bruxism, and trismus. Lowering of mood is an aftereffect that is sometimes reported from 2 to 5 days after a session of ecstasy use. The acute effects of MDMA in ecstasy users have been attributed primarily to increased release and inhibited reuptake of serotonin (5-HT) and norepinephrine, along with possible release of the neuropeptide oxytocin. Repeated or high-dose MDMA/ecstasy use has been associated with tolerance, depressive symptomatology, and persisting cognitive deficits, particularly in memory tests. Animal studies have demonstrated that high doses of MDMA can lead to long-term decreases in forebrain 5-HT concentrations, tryptophan hydroxylase activity, serotonin transporter (SERT) expression, and visualization of axons immunoreactive for 5-HT or SERT. These neurotoxic effects may reflect either a drug-induced degeneration of serotonergic fibers or a long-lasting downregulation in 5-HT and SERT biosynthesis. Possible neurotoxicity in heavy ecstasy users has been revealed by neuroimaging studies showing reduced SERT binding and increased 5-HT2A receptor binding in several cortical and/or subcortical areas. MDMA overdose or use with certain other drugs can also cause severe morbidity and even death. Repeated use of MDMA may lead to dose escalation and the development of dependence, although such dependence is usually not as profound as is seen with many other drugs of abuse. MDMA/ecstasy-dependent patients are treated with standard addiction programs, since there are no specific programs for this substance and no proven medications. Finally, even though MDMA is listed as a Schedule I compound by the Drug Enforcement Agency, MDMA-assisted psychotherapy for patients with chronic, treatment-resistant posttraumatic stress disorder is currently under investigation. Initial results show efficacy for this treatment approach, although considerably more research must be performed to confirm such efficacy and to ensure that the benefits of MDMA-assisted therapy outweigh the risks to the patients. Keywords: MDMA, ecstasy, mood, cognition, neurotoxicity, dependence, PTSD